Development of Islamic Religious Education and Character Education Teaching Materials Based on Minangkabau Local Wisdom - Ikhsan, Messy; Afrinaldi, Afrinaldi (At-Tarbiyat, 2024)
The article “Development of Islamic Religious Education and Character Education Teaching Materials Based on Minangkabau Local Wisdom.” The researcher was interested in taking this title because he was concerned about many young generations experiencing moral decadence, following Western lifestyles, and unfamiliar with local wisdom culture. In addition, no teaching materials or modules contain local wisdom values, in this case, Minangkabau local wisdom. This research and development aims to develop Islamic Religious Education and Character Education teaching modules based on Minangkabau local wisdom through a research and development model. The stages of developing teaching modules based on the 4-D research model consist of Defining, Designing, Developing, and Disseminating—data collection using interview guidelines, observation sheets, tests, and questionnaires. Furthermore, the teaching module is subjected to a validity test, practicality test, and effectiveness test. The results of the validity of the teaching materials for Islamic Religious Education and Character Building based on Minangkabau local wisdom obtained validation of 0.99, declared valid by the assessment of language, media, and material experts. The results of the teacher’s practicality test received a score of 75 with a feasible interpretation, and the results of the student questionnaire obtained a score of 88.67 with a possible interpretation, indicating the practicality of the module. The results of the effectiveness test of the teaching module were considered adequate by obtaining a Sig of 0.000> 0.05. Thus, the Islamic Religious Education and Character Building teaching module based on Minangkabau local wisdom is feasible to implement, develop, and disseminate.